The Importance of Being Consulted - Alessandro Fedele; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
Does management consulting facilitate the access to credit for start-ups? This paper tries to answer the question by developing a theoretical framework where a firm applies for a bank loan to implement a risky project. The probability of success increases if the firm exerts a costly managerial extra-effort, but the bank is unable to observe such an effort: a moral hazard problem may therefore occur. During an economic downturn the project's expected profitability is likely to be low relatively to the effort cost. In this case we find that credit is granted only if the bank hires a management consultant, even when the latter does not improve the business practice.
Keywords: M11; M13; D82; 330